Challenging Assumptions: What Do We Need to Address in Our Disaster Risk Reduction Efforts?. Issue 2 (31st January 2017) - Codreanu, Tudor A.; Ngo, Hanh; Robertson, Andrew; Celenza, Antonio
Abstract: Introduction: Specific knowledge and skills are required, especially in the first 72 hours post-disaster, to bridge the time gap until essential services are restored and Emergency Medical Services (EMS) can focus on individuals' needs. This study explores disaster knowledge and preparedness in the first 72 hours as a function of the individual's engagement in discussions about disasters, and several other factors (both at personal and community/country level), as well as the entities/organizations perceived by the individual as being responsible for disaster risk reduction (DRR) education. Methods: A prospective, cross-sectional survey of 3, 829 final-year high-school students was conducted in nine countries with different levels of disaster risk and economic development. Regression analyses examined the relationship between a 72-hour disaster preparedness composite outcome (ability to make water safe for drinking, knowledge of water potability, home evacuation skill, and improvising a safe room) and a series of independent predictors. Results: Respondents from countries with lower economic development were significantly better prepared for the first 72 hours post-disaster than those from developed countries (OR=767.45; CI=13.75-48, 822.94; P =.001). While several independent predictors showed a significant main effect, combined disaster risk education (DRE) efforts, as a partnership between school and local government, had the best predictive value (OR=3.52; CI=1.48-8.41; P =.005). Conclusions: Disaster preparedness in final-year high-school students is significantly better in developing countries. Further improvement requires a convergent effort in aligning the most effective educational policies and actions to best address the individual's and the community needs. TA Codreanu, H Ngo, A Robertson, A Celenza .Challenging assumptions: what do we need to address in our disaster risk reduction efforts? Prehosp Disaster Med .2017 ;32 (2 ):134 –147 .